Greenhouse gas balance related to conventional and sustainable fruit production systems in the Highlands region of Pasto, Colombia (2016)
This research focused on the greenhouse gas (GHG) emissions and potential sinks associated with conventional and sustainable fruit production systems in the Highlands region of Pasto, Nariño, Colombia. Based on the IPCC (2006) methodologies, the annual emission balance for a 6-year production cycle included agricultural sources and gasoline consumption related to the main agricultural activities and the potential for soil C accumulation and biomass C fixation in all of the studied systems. The multivariate analysis showed that positive GHG balance emissions would be achieved in all sustainable fruit production systems, as compared to conventional fruit production systems with greater impact on (SS1): Rubus glaucus Benth. Associated with Acacia decurrens trees and live coverage of kikuyu Pennisetum clandestinum grass. According to the results of this study, (SS1) showed the beneficial total GHG balance emission accounting for -21,079 kg of atmospheric CO2eq ha-1 yr-1 divided into -4,587 kg CO2eq ha-1 yr-1 and -17,102 kg CO2eq ha-1 yr-1 due an annual soil and biomass C sequestration potential that could help offset its emissions (610 kg CO2eq ha-1 yr-1).